시민들의 소통 플랫폼으로서 서울시 지하철 디지털 사이니지에 적합한 콘텐츠 및 인터랙션 연구 - 강민정(Minjeong Kang); 윤주현(Juhyun Eune) (한국콘텐츠학회 논문지, 17(1), 2017)
As interactive digital signages with computer network have been increasingly popular in public space, the needs for studying content types and interactions suitable for the digital signages are emerging. In this study, we aim to find out what contents are preferred to share and how to interact in the digital signage installed in Seoul subway stations. We conduct a case study, a survey, and an in-depth interview. In the case study, we collect content types which have been communicated in public space. Among these content types, we conduct a survey to find out the preferred contents of Seoul citizens. We observe that the preferred contents differ by the age of the citizens. Specifically, 20's prefer the subjects about personal interests, 40's choose public interests and 30's prefer both types. In addition, we observe that the subjects about personal interest are relatively less preferred when people read, whereas the subjects are preferred when people write. Lastly, regarding interaction type, we find that Seoul citizens prefer touching the screen directly to using smart phone to express their empathy. The contents that people write and the number of likes will be archived as big data and analyzed so that Seoul city officers and citizens will know what people think based on age, location, and subjects. 인터랙션과 네트워크가 가능한 디지털사이니지가 공공장소에 많이 설치가 되면서 이러한 플랫폼에 적합한 콘텐츠에 대한 연구가 대두되었다. 본 연구에서는 지하철에 설치된 디지털사이니지에서 시민들의 소통에 적합한 콘텐츠의 유형과 인터랙션을 밝히는 것을 목표로 하였다. 연구방법으로는 사례연구, 설문조사, 심층 인터뷰를 실시하였다. 사례연구에서는 기존에 공공장소에서 소통되는 콘텐츠 유형과 참여방식을 분석해 보았다. 이를 토대로 설문조사를 하여 서울시 지하철에 설치된 디지털사이니지에서 소통하기 원하는 콘텐츠의 유형과 인터랙션 방향을 밝히고 심층 인터뷰를 통해 연구 결과를 보완하였다. 설문조사 결과 지하철역에 설치된 디지털 사이니지에서 소통하기 원하는 콘텐츠의 유형은 연령대 별로 다른 것으로 나타났다. 우선 20대는 주로 개인적인 글, 40대는 주로 공공의 주제, 그리고 30대는 앞의 두 연령대에서 선호하는 콘텐츠 유형들을 모두 소통하기 원하였다. 소통하고자 하는 콘텐츠를 읽기/쓰기 모드에 따라 나눠서 질문한 결과 두 가지 모드에서 선호하는 콘텐츠 유형은 대체로 유사했지만 일상적인 글 또는 소원과 같은 개인 관련된 글은 읽기에서는 덜 선호하는 것으로 나타났다. 마지막으로 공감표현을 위한 인터랙션을 조사한 결과 시민들은 댓글 보다는 아이콘을 터치하여 표현 하고자 하였고 스마트폰 보다는 스크린에서 직접 터치하는 것을 더 선호하는 것으로 나타났다. 이러한 소통 플랫폼에 저장된 데이터는 지역, 나이, 주제에 따라 분석이 되어 시민들의 생각을 파악하는데 활용될 수 있으리라본다.